The Arabidopsis Proteins AtNHR2A and AtNHR2B Are Multi-Functional Proteins Integrating Plant Immunity With Other Biological Processes - Singh, Raksha; Liyanage, Rohana; Gupta, Chirag; Lay, Jackson O.; Pereira, Andy; Rojas, Clemencia M. (Frontiers in Plant Science, 2020)
AtNHR2A (Arabidopsis thaliana nonhost resistance 2A) and AtNHR2B (Arabidopsis thaliana nonhost resistance 2B) are two proteins that participate in nonhost resistance, a broad-spectrum mechanism of plant immunity that protects plants against the majority of potential pathogens. AtNHR2A and AtNHR2B are localized to the cytoplasm, chloroplasts, and other subcellular compartments of unknown identity. The multiple localizations of AtNHR2A and AtNHR2B suggest that these two proteins are highly dynamic and versatile, likely participating in multiple biological processes. In spite of their importance, the specific functions of AtNHR2A and AtNHR2B have not been elucidated. Thus, to aid in the functional characterization of these two proteins and identify the biological processes in which these proteins operate, we used immunoprecipitation coupled with mass spectrometry (IP-MS) to identify proteins interacting with AtNHR2A and AtNHR2B and to generate their interactome network. Further validation of three of the identified proteins provided new insights into specific pathways and processes related to plant immunity where AtNHR2A and AtNHR2B participate. Moreover, the comprehensive analysis of the AtNHR2A- and AtNHR2B-interacting proteins using published empirical information revealed that the functions of AtNHR2A and AtNHR2B are not limited to plant immunity but encompass other biological processes.